Synopsis of the genus Pseudosparna Mermudes & Monné (Coleoptera, Cerambycidae, Lamiinae), with description of two new species - Monné, Miguel A.; Monné, Marcela L. (Zootaxa, 2014)
Two new species of Pseudosparna Mermudes & Monné, 2009 are described: P. tucurui sp. nov. from Brazil (Pará) and P. pichincha sp. nov. from Ecuador (Pichincha). A key to the species of Pseudosparna is also included.